Hubungan Intensitas Menonton Tayangan Iklan Kosmetik Dengan Minat Membeli Pada Mahasiswa Perguruan Tinggi Swasta - Nurarifiyani, Frida (2016)
An intention to buy is a design form in buying a product before conducting an action to buy a product or a service. The intention to buy can occur if there is stimulus of the product or the service. The intention to buy will occure because of psychological factor that is an intensity of watching a cosmetic advertisement broadcasting. The objective of this research was to know the correlation between the intensity of watching a cosmetic advertisement broadcasting and the intention to buy in the private university students. The method of this research was quantitative with subjects of 106 students. The method of data collection used the psychological scales, they were: the scale of the intensity of watching a cosmetic advertisement broadcasting and the scale of the intention to buy, with the method of insidental sampling. The method of data analysis used product moment. The results of the research showed that there was a very signifiant positive correlation between the intensity of watching a cosmetic advertisement broadcasting and the intention to buy. The higher the intensity of watching a cosmetic advertisement broadcasting, the higher the intention to buy in the students would be. In contrary, the lower the intensity of watching a cosmetic advertisement broadcasting, the lower the intention to buy in the students would be. Meanwhile, the level of intensity of watching a cosmetic advertisement broadcasting and the level of intention to buy in the private university students were categorized as low.